Clinical and radiographic assessment of autogenous dentin nanoparticles in treatment of stage iii periodontitis: a split-mouth clinical study - Enas Ahmed Elgendy,; Ahmed Mohamed Elgendy,; Ola Mohammad ElBorady, (Journal of the Pakistan Medical Association, 2023)
Objective: To compare autogenous dentin nanoparticles with allograft bone grafts in the treatment of stage III periodontitis. Method: The randomised study was conducted at the Department of Oral Medicine and Periodontology, Faculty of Oral and Dental Medicine, Kafrelsheikh University Hospital, Egypt, from January 2021 to January 2022, and comprised adult patients of either gender with stage III periodontitis. Each patient’s bilateral intrabony defect was randomly treated with an allograft on one side and a graft made of dentin nanoparticles on the test side. Each patient’s removed tooth was ground into these nanoparticles. Both groups had their probing pocket depth and clinical attachment loss evaluated at baseline and six months after surgery. Additionally, digital periapical films were collected in both groups at baseline and six months after therapy to assess vertical bone loss. Data was analysed using SPSS 20. Results: Of the 20 patients, 8(40%) were males and 12(60%) were females with overall mean age 31.00±4.06 years (range: 18-50 years). Of the 40 sites, 20(50%) each were in test and control groups. Compared to baseline values, both groups showed significant improvement in probing pocket depth, clinical attachment loss and vertical bone loss postintervention (p<0.05). There was no significant difference between the postoperative outcomes of the two groups (p>0.05). Conclusion: Autogenous dentin nanoparticles were found to be an effective and promising biomaterial for bone regeneration in intrabony defects. Clinical Trial: NCT05258006 link: https://clinicaltrials.gov/ct2/show/NCT05258006, Registration date of the Trial 10/2/2022. Keywords: Bone transplantation, Tuberculin, Autografts, Heterografts, Periodontitis, Nanoparticles, Dentin.